2021
DOI: 10.3390/ijms22105144
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Galectin-3 and Integrins Mediates Cell-Matrix Adhesion in Endothelial Cells and Mesenchymal Stem Cells

Abstract: Galectin-3 (Gal-3) is a β-galactoside-binding protein that influences various cell functions, including cell adhesion. We focused on the role of Gal-3 as an extracellular ligand mediating cell-matrix adhesion. We used human adipose tissue-derived stem cells and human umbilical vein endothelial cells that are promising for vascular tissue engineering. We found that these cells naturally contained Gal-3 on their surface and inside the cells. Moreover, they were able to associate with exogenous Gal-3 added to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…How Gal3 produced by stromal cells can promote BCP-ALL migration is currently not clear, but it could cluster key glycoprotein binding partners such as integrins on the plasma membrane [45] and promote cell polarization and subsequent directed migration. A second possibility is that Gal3 from stroma regulates intracellular events after its uptake by the BCP-ALL cells, as we have previously shown [12] and confirmed (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…How Gal3 produced by stromal cells can promote BCP-ALL migration is currently not clear, but it could cluster key glycoprotein binding partners such as integrins on the plasma membrane [45] and promote cell polarization and subsequent directed migration. A second possibility is that Gal3 from stroma regulates intracellular events after its uptake by the BCP-ALL cells, as we have previously shown [12] and confirmed (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…The KEGG pathways also showed that DEGs were enhanced in cytokine-cytokine receptor interactions and chemokine signaling pathways. Laminin, fibronectin and integrins are known ligands for Gal-3, and therefore, Gal-3 may promote pathological fibrotic processes by regulating cell-cell adhesion and cell proliferation ( 49 , 50 ). Therefore, our study may provide some evidence that Gal-3 plays a multifaceted role in the regulation of inflammatory responses to promote cell-cell interactions and adhesions, which contributes to renal fibrosis that is associated with renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-3 is found in the plasma membrane of cells where it can modulate the interaction between epithelial cells and extracellular matrix or with other cells [ 28 ]. Its ability to bind with integrins or endothelial adhesive proteins allows adhesion with other cells or the promotion of activation of bond cells [ 29 , 30 , 31 , 32 ]. Gal-3 can also bind with glycoproteins to promote extra-cellular matrix binding [ 28 , 33 ] and create a bridge between Gal-3 and cells [ 34 ].…”
Section: Gal-3: a Carbohydrate Binding Protein From The Lectin Familymentioning
confidence: 99%